I Need My Mommy - Irene C. Baird (Adult Education Research Conference, 2006)
Drugs, mandated sentencing, overflowing prisons have negatively affected the lives of 2.3 million children of inmates. This study explored the efficacy of esteem building and parenting perspectives for incarcerated mothers preparing for release.
Keywords: drugs; incarcerated women; parenting